A catalog of Rhagionidae (Diptera: Brachycera) from Chile - González, Christian R; Elgueta, Mario; Santos, Charles Morphy D. (Zootaxa, 2020)
The genera and species of Chilean rhagionids (Diptera: Rhagionidae) are listed, with annotated references to nomenclature, synonymies and generic combinations, type localities, the primary type depositories, distribution, and citations for the most recent revisions. The genus Atherimorpha White is the richest genus in Chile, with 15 described species. Only Leptis basalis Philippi, 1865 is kept as incertae sedis in the family.